As expectativas nos autores pré-keynesianos modernos do mainstrain e na teoria geral - Barros, Leonel Leite (2016)
The theme of expectations in economic sciences is of fundamental importance, but observing, for instance, a Manual of History of Economic Thought has been the idea that the issue only arose from the publication of the General Theory of Employment, Interest and Currency, of the John Maynard Keynes in 1936. The intention of this work is to investigate whether the works of the modern pre-keynesian authors of the mainstream were or not remarks about the expectations and, if so, make your presentation to integrated models of the authors, as well as the topic of discussion in the General Theory, which will enable the understanding of why this work is so relevant in relation to expectations. Thus, to achieve this purpose, it will do a study on the marginalist economists and the School of Cambridge until the advent of General Theory. For this, the first chapter will discuss the expectations models of marginalists authors William Stanley Jevons, Carl Menger, and Léon Walras. The objectives of this chapter shall be: a) to present the discussion of expectations for the marginalist authors; and, b) to indicate the possible cause for the History of Economic Thought have ignored this discussion. In the second and third chapter will discuss the expectations at Cambridge School, the authors to be discussed will be Alfred Marshall, Arthur Cecil Pigou, Dennis Holme Robertson and John Maynard Keynes. The first two will be discussed in the second chapter and the last two in the third. The purpose of the two chapters will be: a) to present the expectations in view of the authors of the Cambridge School; b) to suggest a possible reason for the remarks of Marshall, Pigou and Robertson on the expectations have attracted a lesser extent the attention of the History of Economic Thought regarding the same theme in the General Theory.